2013
DOI: 10.2135/cropsci2012.09.0545
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Drought, Heat, and Combined Drought and Heat Tolerant Donors in Maize

Abstract: Low maize (Zea maysL.) yields and the impacts of climate change on maize production highlight the need to improve yields in eastern and southern Africa. Climate projections suggest higher temperatures within drought‐prone areas. Research in model species suggests that tolerance to combined drought and heat stress is genetically distinct from tolerance to either stress alone, but this has not been confirmed in maize. In this study we evaluated 300 maize inbred lines testcrossed to CML539. Experiments were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
234
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 250 publications
(269 citation statements)
references
References 44 publications
(54 reference statements)
32
234
3
Order By: Relevance
“…In the field, delayed planting can be used to screen for tolerance to heat stress by ensuring higher temperatures are experienced during critical stages of plant growth (Craufurd et al 2013). Using this method Cairns et al (2013) recently reported large genetic variability for tolerance to heat stress in sub-tropical and tropical maize suggesting gains in maize tolerance to heat stress could be achieved through conventional breeding.…”
Section: Reducing the Effects Of Climate Change On Farmers In Maize-bmentioning
confidence: 99%
“…In the field, delayed planting can be used to screen for tolerance to heat stress by ensuring higher temperatures are experienced during critical stages of plant growth (Craufurd et al 2013). Using this method Cairns et al (2013) recently reported large genetic variability for tolerance to heat stress in sub-tropical and tropical maize suggesting gains in maize tolerance to heat stress could be achieved through conventional breeding.…”
Section: Reducing the Effects Of Climate Change On Farmers In Maize-bmentioning
confidence: 99%
“…However, plant breeders have been actively working towards producing cultivars better able to cope with climate change. The Drought Tolerant Maize for Africa project [145] has produced new drought tolerant hybrids [148], and drought tolerant germplasm which also has a higher level of tolerance to higher temperatures is also available [149]. Similarly, the Program for Africa's Seed Systems is seeking to promote the development of seed systems that deliver improved, locally adapted crop varieties to small-scale farmers and the uptake and use of released cultivars [150].…”
Section: Seed Systemsmentioning
confidence: 99%
“…Additionally, simulation studies indicate that maize yield in Africa is likely to be significantly impaired by heat stress (HS; Lobell and Burke, 2010;Lobell et al, 2011), such as can be anticipated as a result of the changes in climate predicted for the coming decades . Moreover, the sensitivity of maize yield to heat is exacerbated under drought conditions (Lobell et al, 2011;Cairns et al, 2012aCairns et al, , 2012bCairns et al, , 2013. Therefore, the development of maize germplasm tolerant to drought and heat conditions is of utmost importance to both increase yields and offset predicted yield losses under projected climate change scenarios (Easterling et al, 2007), especially in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…Therefore, the development of maize germplasm tolerant to drought and heat conditions is of utmost importance to both increase yields and offset predicted yield losses under projected climate change scenarios (Easterling et al, 2007), especially in sub-Saharan Africa. While direct selection for grain yield under DS has resulted in admirable gains in grain yield under stress (Bänziger et al, 2006;Cairns et al, 2013), further improvement requires the incorporation of additional selection traits (Cairns et al, 2012a(Cairns et al, , 2012b. In recent years, genetic and phenotypic markers have been searched extensively for drought tolerance of maize by high-throughput genomic and phenotyping approaches, respectively (Tuberosa and Salvi, 2006;Wen et al, 2011;Araus et al, 2012;Cairns et al, 2013;Prasanna et al, 2013;Araus and Cairns, 2014;Tsonev et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation